Analysis of the effects of immunotherapy depending on cancer subtypes on survival - a single center experience - Rudzińska, Anna; Juchaniuk, Pola; Oberda, Jakub; Ponikowski, Kacper; Gumółka, Paulina; Jakubik, Karol; Jeżak, Mikołaj; Kalicińska, Agnieszka; Doroszewska, Angelika; Janiszewska, Mariola; et al. (Quality in Sport, 2024)
Background: The type of tumor is a huge determinant of survival and treatment outcomes, particularly with immunotherapy, which uses the immune system to target cancer cells. The response to immunotherapy varies depending on tumor types and is influenced by factors such as genetic mutations and the tumor microenvironment. Materials and methods: The present retrospective study analyzed records for 151 patients who underwent immunotherapy at a single center between 2019 and 2023. The cohort included adults diagnosed with solid tumors, primarily NSCLC (non-small cell lung cancer). Immunotherapy agents included pembrolizumab, nivolumab, and others. Data on age, cancer stage, treatment response, adverse events, overall survival (OS), and progression-free survival (PFS) were collected. Statistical analyses, including the Cox proportional hazards model, assessed the impact of tumor types and subtypes on survival outcomes. Results: The median age of the cohort was 69 (SD, 10.3) years, and the majority of the patients were men (64.9%). NSCLC was the predominant tumor type (78.1% of cases). In comparison to adenocarcinoma NSCLC, squamous NSCLC showed a significantly higher hazard ratio (HR) for OS (HR 1.49) and PFS (HR 1.47). Renal cell carcinoma and bladder cancer had lower HRs, suggesting a better prognosis. Conclusions: This study highlights how responses to immunotherapy can differ widely based on tumor type, emphasizing the importance of personalized therapy approaches. These insights underscore the need for further research to tailor immunotherapy more effectively to different cancer types.